2021
DOI: 10.1038/s41598-021-83129-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple micronutrient supplementation improves micronutrient status in primary school children in Hai Phong City, Vietnam: a randomised controlled trial

Abstract: We aimed to determine the efficacy of multiple micronutrient supplementation on the biomarkers of iron, zinc, and vitamin A status across anthropometric status categories in Vietnamese school children. In this 22-week randomised controlled trial, 347 undernourished, normal weight, or overweight/obese children aged 6–9 years were allocated to receive every school day a multiple micronutrient supplement (10 mg iron, 10 mg zinc, 400 µg vitamin A) or a placebo. Haematological indices; circulating ferritin, zinc, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…Iron and zinc have also been found to be involved in appetite regulation, and their supplementation has resulted in improved appetite in young children with evidence of growth faltering in previous studies ( 27 , 31 , 68 ). The prevalence of zinc deficiency in Vietnam is high—estimated to be 51.9 and 12.9% for zinc- and iron-deficiencies, respectively, among children aged 6–75 months in 2009 ( 69 ); and 41.4 and 2.4%, respectively, among children aged 6–9 years in 2016 ( 70 ). In undernourished children, such as in the current study population, prevalence of deficiencies is likely to be higher.…”
Section: Discussionmentioning
confidence: 99%
“…Iron and zinc have also been found to be involved in appetite regulation, and their supplementation has resulted in improved appetite in young children with evidence of growth faltering in previous studies ( 27 , 31 , 68 ). The prevalence of zinc deficiency in Vietnam is high—estimated to be 51.9 and 12.9% for zinc- and iron-deficiencies, respectively, among children aged 6–75 months in 2009 ( 69 ); and 41.4 and 2.4%, respectively, among children aged 6–9 years in 2016 ( 70 ). In undernourished children, such as in the current study population, prevalence of deficiencies is likely to be higher.…”
Section: Discussionmentioning
confidence: 99%
“…Mineral status was not reported in either of these studies and is rarely reported in other similar trials. More commonly, concentrations of plasma minerals and trace elements were assessed after direct use of supplemental micronutrient powders or ready to use foods to increase zinc and iron levels 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Findings regarding the increase in serum zinc level in this study are consistent with the results of previously conducted MNP trials in under-five children [ 37 , 38 ]. A randomized control trial, conducted in Vietnam, found a considerable reduction (17.3%) in the plasma zinc level in 6–9-year-old children [ 39 ]. A study conducted by García-Guerra et al, which examined the impact of MNP supplements on the serum zinc levels of infants aged 6–12 months, administered 6 days per week for 4 months, showed a significant increase in plasma zinc level [ 40 ].…”
Section: Discussionmentioning
confidence: 99%